Hereditary spastic paraplegia: clinico-pathologic features and emerging molecular mechanisms - Fink, John K. (2013)
Hereditary spastic paraplegia (HSP) is a syndrome designation describing inherited disorders in which lower extremity weakness and spasticity are the predominant symptoms. There are more than 50 genetic types of HSP. HSP affects individuals diverse ethnic groups with prevalence estimates ranging from 1.2 to 9.6 per 100,000 [39, 70, 77, 154, 185]. Symptoms may begin at any age. Gait impairment that begins after childhood usually worsens very slowly over many years. Gait impairment that begins in infancy and early childhood may not worsen significantly. Post mortem studies consistently identify degeneration of corticospinal tract axons (maximal in the thoracic spinal cord) and degeneration of fasciculus gracilis fibers (maximal in the cervico-medullary region). HSP syndromes thus appear to involve motor-sensory axon degeneration affecting predominantly (but not exclusively) the distal ends of long central nervous system (CNS) axons. In general, proteins encoded by HSP genes have diverse functions including axon transport (e.g. SPG30/KIF1A, SPG10/KIF5A and possibly SPG4/Spastin); endoplasmic reticulum morphology (e.g. SPG3A/Atlastin, SPG4/Spastin, SPG12/reticulon 2, and SPG31/REEP1, all of which interact); mitochondrial function (e.g. SPG13/chaperonin 60/heat shock protein 60, SPG7/paraplegin; and mitochondrial ATP6; 4) myelin formation (e.g. SPG2/Proteolipid protein and SPG42/Connexin 47); 5) protein folding and ER-stress response (SPG6/NIPA1, SPG8/K1AA0196 (Strumpellin), SGP17/BSCL2 (Seipin) [113-115], “mutilating sensory neuropathy with spastic paraplegia” due to CcT5 mutation and presumably SPG18/ERLIN2); 6) corticospinal tract and other neurodevelopment (e.g. SPG1/L1 cell adhesion molecule and SPG22/thyroid transporter MCT8); 7) fatty acid and phospholipid metabolism (e.g. SPG28/DDHD1, SPG35/FA2H, SPG39/NTE, SPG54/DDHD2, and SPG56/CYP2U1); and 8) endosome membrane trafficking and vesicle formation (e.g. SPG47/AP4B1, SPG48/KIAA0415, SPG50/AP4M1, SPG51/AP4E, SPG52/AP4S1, and VSPG53/VPS37A). The availability of animal models (including bovine, murine, zebrafish, Drosophila, and C. elegans) for many types of HSP permits exploration of disease mechanisms and potential treatments. This review highlights emerging concepts of this large group of clinically similar disorders. For recent review of HSP including historical descriptions, differential diagnosis, and additional references see [78].